The Effect of Working Capital Turnover, Liquidity, Leverage and Company Size on Profitability - Setiawan, Eka Bagus; Sukesti, Fatmasari; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to empirically test Working Capital Turnover, Liquidity, Leverage and Company Size on Profitability. The data used in this study are secondary data and the companies used as sample criteria are selected based on the purposive sampling method. The sample in this study is manufacturing companies in the consumer goods sector listed on the IDX for the 2020-2022 period. From this population, the number of companies that met the criteria to be used as a sample was 36 companies which were then multiplied by the 3-year research period to 108 samples. The data analysis methods used are descriptive statistics, classical assumption tests, multiple linear regression analysis and hypopotential tests. The results using the F test show that Working Capital Turnover, Liquidity, Leverage, and Company Size have a significant influence on Profitability. The determination coefficient indicated by the adjusted Rsquare value is 0.208. This means that 20.8% of the dependent variables, namely Proftability, can be explained by four independent variables of Working Capital Turnover, Liquidity, Leverage and Company Size, while the remaining 70.2% is explained by other variables or causes outside the model. Partially, using the t-test, it was concluded that some of the variables of Working Capital Turnover and Leverage did not have a significant effect on Profitability, while the variables of Liquidity and Company Size had a significant effect on Profitability.